On extending endomorphisms to automorphisms - Hilbert Levitz; Warren Nichols (International Journal of Mathematics and Mathematical Sciences)
A monic endomorphism of a structure A can be extended to an automorphism of a larger structure A*. We investigate which properties are preserved by this process.